New Cities In Urban And Regional Development Planning Oyesiku K; Lagos, Nigeria. Longman (2010) Pp 353. Isbn 978 978 026 3577 (Paper Back) Includes Index, Photos, Notes, Tables And Figures, Appendix And References. Price N1,500.00. Approx. 10.00. - Mohammed Olaitan Lawal (Faculty of Geography, Universitas Gadjah Mada, 2014)
For a long time, cities have been regarded as the main source of economic growth and development. However, increased size and density of cities have generated high land costs, rent and transport cost, congestion and pollution, and increased social disorganization. The condition is even worse in developing countries – urban migration, over-utilization of housing and infrastructure, persistent slums, and squatter settlements. This books represents a comparative study between the USA and Nigeria related to characteristics of the cities in both countries. This book tries to address the question “How has the United States of America and Nigeria have been able to address the problems of ‘swollen’ cities and metropolitan growth?”. Outcome of several planned new communities and cities in both countries is of paramount importance to the contribution of knowledge on physical planning approaches globally. The most significant discussion are shown in the final chapter, by giving examples of policy implications and comments on new cities in national and regional development as well as urban and regional development and planning strategy in the global context.